2011
DOI: 10.1186/1743-422x-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of H5N1 virus in mice attenuates after in vitro serial passages

Abstract: The virulence of A/Vietnam/1194/2004 (VN1194) in mice attenuated after serial passages in MDCK cells and chicken embryos, because the enriched large-plaque variants of the virus had significantly reduced virulence. In contrast, the small-plaque variants of the virus and the variants isolated from the brain of mice that were infected with the parental virus VN1194 had much higher virulence in mice. The virulence attenuation of serially propagated virus may be caused by the reduced neurotropism in mice. Our whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The mutations of H5 RBD affect not only the viral binding avidity but also the pathogenicity of virus, though the determinants of virulence were usually focused on the NA‐1 and polymerase genes. Our previous studies have indicated the specific mutations in PB1 and PB2 of H5N1 viruses contributed to the upregulated proliferation and attenuation in virulence to mice [Li et al, , ]. In the present study, a recombinant VN1194 virus which carrying mouse lung‐adapted mutation E190G in HA was confirmed to reduce viral replication in vitro and attenuated VN1194 virus in mice.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The mutations of H5 RBD affect not only the viral binding avidity but also the pathogenicity of virus, though the determinants of virulence were usually focused on the NA‐1 and polymerase genes. Our previous studies have indicated the specific mutations in PB1 and PB2 of H5N1 viruses contributed to the upregulated proliferation and attenuation in virulence to mice [Li et al, , ]. In the present study, a recombinant VN1194 virus which carrying mouse lung‐adapted mutation E190G in HA was confirmed to reduce viral replication in vitro and attenuated VN1194 virus in mice.…”
Section: Discussionsupporting
confidence: 68%
“…VN1194 is also highly pathogenic in mice. Mouse model is one of the models of mammalian infection used to assess the pathogenic mechanism and virulence of H5N1 influenza viruses [Li et al, 2011b]. In the current study, the prototype of H5N1 clinical isolate, A/Vietnam/ 1194/2004, had no prior history of mouse passage.…”
Section: Introductionmentioning
confidence: 97%
“…This was previously shown, not only in vitro (2), but also for natural isolates (reviewed in reference 26). Different studies provided hints of the impact of the so-called internal proteins on pathogenicity (16,25). The data presented here additionally imply a possible role of the internal proteins in immunoescape.…”
Section: Discussionmentioning
confidence: 80%
“…One drawback of our system, of course, is the attenuation of the isolates, as reflected in the IVPI. Possibly, this attenuation is caused by alterations in the viral polymerase proteins, as recently speculated (25). In addition, transmissibility as a property of the virus may be reduced without undermining the virus' success in infecting cells, because transmission is guaranteed by the passaging system.…”
Section: Discussionmentioning
confidence: 98%
“…And our previous study showed that the rescued VN1194, i.e. rVN1194, with C 4 at PB2, PB1 and PA, while U 4 at the other five segments was as high pathogenic as the wild VN1194 virus, with an MLD 50 less than 1 PFU [19], [33]. Because the difference in pathogenicity contributed by the U4/C4 variation in PB1 was not large enough to be identified in the background of rVN1194 (data not shown), we re-rescued the VN1194 virus with C 4 in all segments, which was named as rVN-PB1(C).…”
Section: Discussionmentioning
confidence: 92%